Study of the variation in mechanical properties of the Al-Mg-Si alloy with ageing time (International Seven Journal of Multidisciplinary, 2024)
Aluminum alloys are increasingly being used in industry, so it is necessary to study their processing and chemical composition in order to understand and improve their mechanical properties. This work aims to analyze the chemical composition of an Al-Mg-Si alloy and the effects that solubilization and aging heat treatments at different times have on its mechanical and microstructural characteristics. Tensile and Vickers microhardness tests were carried out to obtain the mechanical properties of the factory material, after which the material was subjected to solubilization at 530 °C for 40 minutes and aging at 180 °C for 0.5, 1, 2, 4, 6 and 8 hours and the Vickers microhardness of the material for each aging time. Metallographic analyses were carried out on the material at the factory, after 4 and 8 hours of ageing. The microhardness results were compared, allowing the ageing curve of the material to be plotted and the influence of ageing time on the mechanical properties of the alloy to be observed.